PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIIB SMP NEGERI 1 SUNGAI LALA - Antin Nisa Siswika; Syofni Syofni; Sakur Sakur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Data daily test results of students of class VIIB SMP Negeri 1 Sungai Lala provide information that the percentage of learners who reach the criteria masses of mminimum is still low. This Study aims to improve the learning process and the student’s outcomes of mathematic learning by applying problem based learning model. This cclassroom action research with two cycles was conducted in class VIIB SMP Negeri 1 Sungai Lala in the second semester of academic year 2018/2019 to 32 students.The required data are teacher and students activities, collected by observation technique and analyzed by descriptive narative analysis, and data of the students evaluation collected by tes technique and analyzed by descriptive statistics analysis. Statistics descriptive analysis shows that students mathematics learning outcomes improved from the basic score to the Quiz I, from Quiz I to Quiz II. This study concludes is implementation of problem based learning improved the learning process and the student’s outcomes of mathematic learning at class VIIB SMP Negeri 1 Sungai Lala in the second semester of academic year 2018/2019.Key Words: Problem Based Learning, Outcomes of Mathematic Learning, Learning Process